The modified Fluid Particle Model for non-linear Casson fluid and its parallel distributed implementation - Paszyński, M.; Schaefer, R. (Computer methods in applied mechanics and engineering, 2005)
The classical Fluid Particle Model (FPM), invented by Español, has been designed to simulate linear Newton fluid flow. We will present a modification of the FPM that allows to simulate flows for a class of fluids described by a non-linear constitutive equation. The inter-particle interaction parameters are adjusted for the locally variable viscosity. The method has been applied to simulate the blood flow in arteries, with a focus on capturing the pulse wave propagation. The blood has been modeled by the non-linear Casson law. Numerical results compare favorably with experimental data for the carotid artery. Details of a parallel implementation of the algorithm will also be presented.